2015
DOI: 10.1007/s00125-015-3719-0
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acids from fat cell lipolysis do not activate an inflammatory response but are stored as triacylglycerols in adipose tissue macrophages

Abstract: Aims/hypothesis Activation of macrophages by fatty acids (FAs) is a potential mechanism linking obesity to adipose tissue (AT) inflammation and insulin resistance. Here, we investigated the effects of FAs released during adipocyte lipolysis on AT macrophages (ATMs). Methods Human THP-1 macrophages were treated with media from human multipotent adipose-derived stem (hMADS) adipocytes stimulated with lipolytic drugs. Macrophages were also treated with mixtures of FAs and an inhibitor of Toll-like receptor 4, sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 49 publications
(55 reference statements)
1
27
1
Order By: Relevance
“…In rat, taurine could increase liver CD36 expression (Li, Reynolds, Sloboda, Gray, & Vickers, ) that contributed to the uptake of oleate only in the PI and MI, but not in the DI (Nassir, Wilson, Han, Gross, & Abumrad, ). A study reported that oleate could increase IL‐10 secretion in the THP‐1 macrophages of human (Casparbauguil et al, ). Hence, we propose that taurine supplementation might contribute to the uptake of oleate only in the PI and MI (rather than in the DI), leading to the up‐regulated IL‐10 mRNA levels only in the PI and MI (rather than in the DI) of fish.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In rat, taurine could increase liver CD36 expression (Li, Reynolds, Sloboda, Gray, & Vickers, ) that contributed to the uptake of oleate only in the PI and MI, but not in the DI (Nassir, Wilson, Han, Gross, & Abumrad, ). A study reported that oleate could increase IL‐10 secretion in the THP‐1 macrophages of human (Casparbauguil et al, ). Hence, we propose that taurine supplementation might contribute to the uptake of oleate only in the PI and MI (rather than in the DI), leading to the up‐regulated IL‐10 mRNA levels only in the PI and MI (rather than in the DI) of fish.…”
Section: Discussionmentioning
confidence: 99%
“…In rat, taurine could increase liver CD36 expression (Li, Reynolds, Sloboda, Gray, & Vickers, 2013) that contributed to the uptake of oleate only in the PI and MI, but not in the DI (Nassir, Wilson, Han, Gross, & TA B L E 5 Correlation coefficient of parameters between signal molecules and inflammatory cytokines, as well as signal molecules themselves in proximal intestine (PI), mid intestine (MI) and distal intestine (DI) of young grass carp (Ctenopharyngodon idella) fed the all-plant protein source-based diets containing graded levels of taurine Abumrad, 2007). A study reported that oleate could increase IL-10 secretion in the THP-1 macrophages of human (Casparbauguil et al, 2015). Hence, we propose that taurine supplementation might contribute to the uptake of oleate only in the PI and MI (rather than in the DI), leading to the up-regulated IL-10 mRNA levels only in the PI and MI (rather than in the DI) of fish.…”
Section: Taurine Supplementation Attenuated Inflammation In the Intmentioning
confidence: 99%
“…The authors suggested that other mechanisms may link dietary fat intake with TLR‐associated pathologies . The view that FFAs from adipocytes did not stimulate cytokine release from macrophages has recently been confirmed by experimental observations . Moreover, the RBP4 (a retinol transporter secreted from adipocytes and liver) is also involved in AT inflammation .…”
Section: Adipose Tissue Inflammationmentioning
confidence: 96%
“…Moreover, SFAs and their derivatives, including ceramides, are classified as danger-associated molecular patterns (DAMPs) that are recognised by the NLRP3 inflammasome and lead to IL-1β secretion via caspase 1 activation [ 142 ]. However, the response of macrophages upon lipid uptake does not necessarily have to be proinflammatory in nature [ 143 ]. Although it has been suggested that internalised palmitate, a very well-known SFA, promotes lipid metabolism and limits inflammation [ 57 ], in general only unsaturated FAs, particularly n -3 FAs, are recognised for their anti-inflammatory properties [ 139 , 144 ].…”
Section: Drivers Of the Adipose Tissue Macrophage Phenotypementioning
confidence: 99%